Investigation of the Relationship Between TAFI Plasma Levels and Hemorrhage in Patients with Crimean-Congo Hemorrhagic Fever and the Role of TAFI in the Disease Pathogenesis - Şengül Aşkın, Hüsna; Parlak, Mehmet; Laloğlu, Esra; Yılmaz, Sinan; Aşkın, Lütfü; Parlak, Emine (Cerrahpaşa Medical Journal, 2021)
Objective: Crimean-Congo hemorrhagic fever is a tick-borne viral infection presenting with fever and bleeding. Thrombin-activatable fibrinolysis inhibitor is a plasma procarboxypeptidase synthesized in the liver, causing downregulation of fibrinolysis. The association of thrombin-activatable fibrinolysis inhibitor levels with the clinical course and pathogenesis of Crimean-Congo hemorrhagic fever has not been adequately studied. The aim of the current study was to determine plasma thrombin-activatable fibrinolysis inhibitor levels in patients with Crimean-Congo hemorrhagic fever, and to reveal its role in the clinical course of the disease and in the pathogenesis of hemorrhage. Methods: Forty-four patients diagnosed with Crimean-Congo hemorrhagic fever and 44 control subjects were included in the study. The diagnosis of Crimean-Congo hemorrhagic fever was based on a positive result for IgM antibodies or Crimean-Congo hemorrhagic fever virus detected by PCR. The thrombin-activatable fibrinolysis inhibitor levels were analyzed. Results: The mean age and sex distribution were similar between the groups. The white blood cell, prothrombin time, activated partial thromboplastin time, and international normalized ratio values were also comparable (P > .05). The mean plasma thrombin-activatable fibrinolysis inhibitor value was 429.33 ± 328.224 ng/mL in the Crimean-Congo hemorrhagic fever group, and 922.44 ± 1236.449 ng/mL for the control group (P = .045). Conclusion: Reduced thrombin-activatable fibrinolysis inhibitor levels were found in Crimean-Congo hemorrhagic fever patients. Decreased thrombin-activatable fibrinolysis inhibitor levels may contribute to the impairment of the coagulation mechanism. In other words, thrombin-activatable fibrinolysis inhibitor may be involved in the pathogenesis of bleeding in Crimean-Congo hemorrhagic fever. Cite this article as: Şengül Aşkın H, Parlak M, Laloğlu E, Yılmaz S, Aşkın L, Parlak E. Investigation of the Relationship Between TAFI Plasma Levels and Hemorrhage in Patients with Crimean-Congo Hemorrhagic Fever and the Role of TAFI in the Disease Pathogenesis. Cerrahpaşa Med J. 2021;45(2):101-106.